2006
DOI: 10.1007/11963516_5
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony and Asynchrony in Membrane Systems

Abstract: Abstract. We consider synchrony and asynchrony in the behaviour of various models of membrane systems, which may differ in the way individual reactions are defined as well as in the way multisets of these reactions can be executed in a single computational step. We concentrate on the properties of ongoing computations, including the unbounded ones. Our focus is on the properties of system states involved in such computations as well as on concurrency and causality relationships between executed reactions. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The reader might wonder whether similar one-to-one translations are also possible for other extensions of the basic membrane system model. An initial investigation is reported in [14] where membrane systems with reaction rules that may become obsolete or available depending on the changing structure of the cells are discussed, as are membrane systems with permeable or with dissolving membranes. It appears that such extensions do not lend themselves to one-to-one translations to Petri nets, although there is a way of modelling of their salient features using the translation to PTLAI-nets in combination with special control structures.…”
Section: Discussionmentioning
confidence: 99%
“…The reader might wonder whether similar one-to-one translations are also possible for other extensions of the basic membrane system model. An initial investigation is reported in [14] where membrane systems with reaction rules that may become obsolete or available depending on the changing structure of the cells are discussed, as are membrane systems with permeable or with dissolving membranes. It appears that such extensions do not lend themselves to one-to-one translations to Petri nets, although there is a way of modelling of their salient features using the translation to PTLAI-nets in combination with special control structures.…”
Section: Discussionmentioning
confidence: 99%
“…We have also attempted a number of transformations between Communicating X-Machines and P Systems and vice-versa [19,23]. Others in the P system research community showed more interest in other transformations, such as from P Systems to Petri nets [25], process algebra [6], cellular automata [7] etc. These have not only demonstrated the equivalence of these methods but created a temptation to try out several techniques known for one method to the other.…”
Section: Synthesised Methods and Transformationsmentioning
confidence: 99%
“…One of the research line in membrane systems is to connect mobile membranes with process calculi; e.g., [31], Petri nets [2], [45], cellular automata [34] and communicating X-machines [44]. Several studies focused on the relationships between these models in order to use their techniques and results: e.g., model checking of process calculi, invariants of Petri nets, testing methods of X-Machines.…”
Section: Relationships With Other Approachesmentioning
confidence: 99%